Pengaruh Emotional Branding terhadap Loyalitas Pelanggan pada Toko Central Perabot Kupang: Studi Kasus pada Produk Elektronik Merek Miyako - Ndolu, Steven Yudson; Nggandung, Yeheskial; Loe, Andri Paulus (Journal Economic Education, Business and Accounting, 2025)
Abstract: The numerous factors that consumers take into account when selecting brand of Miyako product are the driving force behind this study. This study aims to ascertain the partial and simultaneous effects of brand image and brand awareness on customer loyalty at the Centarl Perabot Kupang shop. This study employed a quantitative research design with a sample size of thirty samples and data gathering methods that included literature reviews, interviews, and questionnaires. Instrument trials were carried out to determine the validity and reliability of the measuring devices. The product moment correlation technique was used to test the validity of the instruments, the Cronbach Alpha technique was used to test their reliability, and SPSS V 21.0 was used to assist with data analysis using multiple linear regression. The study's findings show that: 1. Customer loyalty is impacted by brand awareness; 2. Customer loyalty is impacted by brand image. 3. Customer loyalty is impacted by both brand image and brand awareness at the same time. The two independent variables' coefficient of determination (R2) is 0.616, or 61.6% of consumer loyalty.